Discussion of the Conceptual Model of Debris Flow and Flexible Dikes in the Carachacra Creek - Gutiérrez, Rubén Esaú Mogrovejo (2025)
In this paper, the first analysis of the conceptual model of this non-Newtonian flow, poses the first challenge of proposing an initial discussion of the geometric, kinematic and dynamic characteristics of this flow that each water cycle converges in the Carachacra stream in Peru, it has been identified in the field that this mixture reaches a sedimentation bank greater than 6 m, and as support to validate and compare the Flo-2d computational tool was used, which has allowed us to obtain not only the maximum draft but also the velocity and the resulting impact forces. Therefore, by means of the previous results, we projected the imperative need to contemplate flexible dikes in three strategic zones, such as Agua Salada Creek, Antioquia Creek and the lower part of Carachacra Creek. After the discussion of the conceptual flow model and the technical characteristics of the flexible levees, it was suggested the implementation of the UX 120-H6 model with a height of 6.8m, a fill length between 42 to 70 m, and a variable width between 24 to 42m, this geometry would be adequate to contain the volume of this mixture for a 500-year event, obtaining a height of 4.5m, velocity 2m/s and impact force of 63KN/m.